Neural recruitment and cognitive aging: two hemispheres are better than one, especially as you age. - Reuter-Lorenz, Patricia A.; Stanczak, Louise; Miller, Andrea C. (Psychological Science., 1999)
The writers test the hypothesis that neural recruitment compensates for age-related neural declines in a visual laterality analysis that explored age differences in the efficiency of bihemispheric processing. They explain that letter-matching tasks of varying complexity were performed under two conditions: matching letters projected to the same visual field (hemisphere) and matching letters projected to opposite visual fields. They assert that as predicted by the recruitment hypothesis, older adults generally performed better in the bilateral than in the unilateral condition, whereas young adults displayed this pattern only for the most complex task. They consider the relation between these findings and neuroimaging evidence for recruitment and the relevance of the present bihemispheric advantage to other evidence for age-related changes in interhemispheric transfer.